2005
DOI: 10.2174/138920005774330666
|View full text |Cite
|
Sign up to set email alerts
|

CYP1A1 Is a Major Enzyme Responsible for the Metabolism of Granisetron in Human Liver Microsomes

Abstract: Granisetron, a potent 5-HT3 receptor antagonist, has been reported to be mainly metabolized to 7-hydroxygranisetron and a lesser extent to 9'-desmethylgranisetron in humans. A previous study indicated that cytochrome P450 (CYP)3A4 is a major catalyst of 9'-demethylation, although the major CYP isoform(s) responsible for 7-hydroxylation are unknown. To clarify granisetron 7-hydroxylase, the in vitro metabolism of granisetron using expressed human CYPs and human liver microsomes was investigated. 7-Hydroxygranis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 16 publications
1
27
0
Order By: Relevance
“…Since many tissues exhibit esterase activity it is not surprising that predicted CL from hepatic metabolism underestimates total CL (predicted CL 6 vs observed Cl 18.8 ml/min/kg). Similarly granisetron is reported to be primarily metabolised by the extra hepatic CYP1A1 [29]. These examples exemplify the importance of a priori elucidation of metabolite routes and reaction phenotyping for candidate drugs.…”
Section: Prediction Of Pk Parameters Clearancementioning
confidence: 92%
“…Since many tissues exhibit esterase activity it is not surprising that predicted CL from hepatic metabolism underestimates total CL (predicted CL 6 vs observed Cl 18.8 ml/min/kg). Similarly granisetron is reported to be primarily metabolised by the extra hepatic CYP1A1 [29]. These examples exemplify the importance of a priori elucidation of metabolite routes and reaction phenotyping for candidate drugs.…”
Section: Prediction Of Pk Parameters Clearancementioning
confidence: 92%
“…20,21) It has been previously reported that granisetron 7-hydroxylation, a major metabolic pathway, is almost exclusively catalyzed by CYP1A1 in human liver microsomes. 20) The potent inhibition of CYP1A1 by CBD might influence the pharmacokinetics of granisetron.…”
Section: Discussionmentioning
confidence: 99%
“…20,21) It has been previously reported that granisetron 7-hydroxylation, a major metabolic pathway, is almost exclusively catalyzed by CYP1A1 in human liver microsomes. 20) The potent inhibition of CYP1A1 by CBD might influence the pharmacokinetics of granisetron. At present, however, the roles of CYP1A1 and CBD-mediated inhibition in drug clearance are limited because of a limited number of drugs metabolized by CYP1A1 and very low constitutive expression of CYP1A1 in the liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CYP1A1-mediated N-hydroxylation and O-dealkylation of riluzole proceeds at a lower K m and a higher biotransformation rate than the hepatic metabolism of this compound by CYP1A2 [180]. CYP1A1 also plays a role in the metabolism of another neuroactive drug, granisetron [181]. Granisetron, a serotonin 5-HT3 receptor antagonist used to treat chemotherapyinduced nausea and vomiting, is metabolized primarily by CYP1A1 to 7-hydroxygranisetron and to a lesser degree to 9â€Č-desmethylgranisetron by CYP1A1 and CYP3A4.…”
Section: Vitamin a [219] Nutrientmentioning
confidence: 99%